PPOS Protocol Effectively Improves the IVF Outcome Without Increasing the Recurrence Rate in Early Endometrioid Endometrial Cancer and Atypical Endometrial Hyperplasia Patients After Fertility Preserving Treatment - Chen, Jiazhou; Cheng, Yali; Fu, Wei; Peng, Xiandong; Sun, Xiaoxi; Chen, Hua; Chen, Xiaojun; Yu, Min (Frontiers in Medicine, 2021)
Objective: To investigate the effectiveness and recurrence risk of different ovulation stimulation protocols in early-stage endometrioid endometrial cancer (EEC) and atypical endometrial hyperplasia (AEH) patients after successful fertility preserving treatment. Design: A retrospective review of clinical files between June 2012 and July 2018. Setting: University hospital. Patients: 97 women (74 AEH and 23 early-stage EEC patients) underwent in vitro fertilization (IVF) and frozen-thawed embryo transfer (FET) after successful fertility preserving treatment. All patients received megestrol acetate which was initiated immediately after AEH or EEC diagnosis by hysteroscopy. Fertility treatment was initiated after confirmation of complete response by two consecutive hysteroscopic evaluations and endometrium biopsy in a three-month interval. Women with tubal factors underwent IVF treatment directly. Women who failed to conceive spontaneously within 12 months or after other infertility treatments like ovulation induction for 6 consecutive months or 2 consecutive artificial insemination failures were also offered IVF treatment. Main Outcome Measure (s): The clinical and laboratory embryo data, clinical pregnancy outcomes and endometrial disease recurrence rates. Results: Compared with the standard regimen group, the good-quality embryo rate was higher in progestin primed ovarian stimulation (PPOS) regimen group (P=0.034). Univariate analysis showed significant differences in age (P=0.033), treatment time of endometrial lesions (P<0.001), and duration of Gn treatment (P=0.018) between the recurrent and non-recurrent groups. In the adjusted model of multivariate logistic regression analysis, the age (P=0.014) at ovulation induction and treatment time of endometrial lesions (P<0.001) were significantly correlated with the recurrence of endometrial disease. Conclusions: The PPOS protocol is a feasible and safe strategy to stimulate ovulation during IVF after fertility preservation therapy, and the age at ovulation induction and treatment time of endometrial lesions are two stable predictors of recurrence in endometrial diseases.